A new insectivoran-like metatherian from western Argentina (Quebrada Fiera, Mendoza Province, Deseadan Age, late Oligocene) - Forasiepi, Analía (2010)
A new metatherian was recently found in the Quebrada Fiera locality (southern Mendoza Province, Argentina), in late Oligocene deposits (Agua de la Piedra Formation; Deseadan SALMA). The specimen consists of fragments of both dentaries, the right maxilla, and a fragment of the left premaxilla with dentition, all belonging to a single, subadult individual. The teeth are represented by seven upper and lower antemolars and at least three molars, with an inferred dental formula of I/I?3/3, C/c1/1, P/p3/3, M/m?3/?3. Among the most conspicuous dental features are worth mentioning the following: caniniform-like first upper incisor; enlarged and flattened second and third upper incisors; large, procumbent first lower incisor; a single deciduous tooth in the upper and lower dentitions with complex morphology; upper molars with a broad stylar shelf bearing a tall StB (slightly lower than metacone) and StD; parastyle developed at the end of the anterior cingulum, which is lower than the stylar shelf; hypoconelike talon, basal to the protocone at least in the M1; lower molars with reduced, low paraconid which is located close to the mid portion of the trigonid; low metaconid appresed to the protoconid in m1 and slightly distant in m2; columnar entoconid without the associated preentocristid; extremely reduced hypoconulid in median position, and lack of posterior cingulum. The new specimen has a unique combination of features among metatherians and other mammalian lineages of Deseadan age, including the well-known faunas from Patagonia. Several features are strongly convergent with erinaceomorphans, such as the presence of a large and procumbent first lower incisor, hypocone-like talon, and median hypoconulid. Its phylogenetic affinities are difficult to establish a priori, even though features of the dentition suggest probable derorhynchid ("Didelphimorphia") affinities.